Modelamiento geomecánico para la reducción de la incertidumbre del macizo rocoso, utilizando técnicas geoestadísticas en el estudio de prefactibilidad del Túnel Nazareth, cía. minera San Rafael 2019 - Sandoval Custodio, Rubén Javier (2019)
This thesis addresses one of the factors that are taken into account within the phase of study and execution of a project, the quality characteristics of the rock mass on which an underground excavation will be carried out, normally the geological interpretation of the faults is made , gaps and dikes that are raised by the geology area. Within the works of expansion of reserves executed by any mining company, drillings are made, which provide information on the structures present in the rock mass and if they are economically profitable, the proposal is to make use of the recovered witnesses to obtain the necessary information such as RQD, compressive strength and with the theoretical models proposed by Bienawsky, Bartón and others, to be able to relate it to the quality of the rock mass and through it to develop a geomechanical model making use of statistical and geostatistical techniques, to in order to obtain a zoning based on the quality of the rock mass using RMR89. In the proposed work sequence, first of all the laboratory evaluation of the witnesses is done to obtain the RQD by characterizing it, which is then complemented with laboratory data to obtain the RMR by sections, which will help us to prepare our geomechanical model (instead of laws, geomechanical valuation will be used). To have a greater certainty of the information entered, the evaluation is done in software, to verify that the data is statistically correct, errors were obtained which were corrected, in order to make use of the variograms that allow us to see the scope of our model and the degree of certainty we have. Specifically the composition gives us the dimensions of the blocks to be used in the model that was 3.0 m x 3.0 m x 3.0 m, but for operational issues the dimensions of 5.0 m x 5.0 m x 5.0 m were taken, resulting in a geomechanical model that is far from the geological model, where it is appreciated that the quality of the rock mass at that depth is Good (Class II) and Regular (Class III), as well as throughout the area of influence of the project, the faults are appreciated but do not become significant, It does not mean that they disappear, but that they do not influence the quality of the rock mass.